2016
DOI: 10.3390/jcm5030037
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Crossroads between EMT and Stemness in the Context of Cancer

Abstract: The epithelial-mesenchymal transition (EMT) is an example of cellular plasticity, where an epithelial cell acquires a mesenchymal-like phenotype that increases its migratory and invasive properties. Stemness is the ability of stem cells to proliferate in an asymmetric way that allows them to maintain the reservoir of undifferentiated cells with stem cell identity, but also to produce new differentiated cells. Initial works revealed that activation of the EMT program in epithelial cells induces the acquisition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 86 publications
1
94
0
Order By: Relevance
“…Stemness is also associated with EMT. In the procession of EMT in epithelial cells, the stem cell properties increased . Our study demonstrated that chronic ethanol exposure promoted stemness of HCC cells which was accompanied by enhanced with EMT.…”
Section: Discussionmentioning
confidence: 58%
“…Stemness is also associated with EMT. In the procession of EMT in epithelial cells, the stem cell properties increased . Our study demonstrated that chronic ethanol exposure promoted stemness of HCC cells which was accompanied by enhanced with EMT.…”
Section: Discussionmentioning
confidence: 58%
“…Third, activation of EMT in injury and many other situations is frequently associated with activation of genes typical of stem cell states, and increased stemness (Liao & Yang, ; reviewed in Fabregat, Malfettone, & Soukupova, ). Stemness is associated with loosened phenotypic restrictions and enhanced plasticity.…”
Section: Adaptive Cellular Reprogrammingmentioning
confidence: 99%
“…The EMT/stemness association is shown for instance by the findings that typical inducers of EMT, such as Snail, Slug, or TGFβ, also activate stem cell properties (Mani et al, ; Morel et al, ). A stem cell‐like phenotype is also induced by other EMT inducers, including Zeb and Twist (reviewed in Fabregat et al, ). In line with this, invasive tumor cells express both EMT and stemness characteristics (reviewed in Jordan, Johnson, & Abell, ; Rhim et al, .…”
Section: Adaptive Cellular Reprogrammingmentioning
confidence: 99%
“…Aggressive tumor progression and poor therapeutic outcomes have been attributed to characteristic cellular plasticity due to abnormal elevation of EMT-TFs [41]. Expression of EMT-TFs is repressed in somatic tissues but reactivated during cancer development by a variety of cell-autonomous pathways and microenvironmental cues [50].…”
Section: Regulation Of Emt-tfsmentioning
confidence: 99%